2021
DOI: 10.22159/ijap.2021.v13s2.12
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Substance Produced by a Soil Bacteria Isolated From Rhizosphere of Zingiber Officinale

Abstract: Objective: In our previous study, we have found many isolates of bacteria from Zingiber officinale rhizosphere in Magelang, Central Java, Indonesia. J4, one of the isolates, has been found to contain metabolites which have antibacterial activity. The active chemical compound was unidentified. This study aims to identify the molecular formula of the active compound which has potential antibacterial activity. Methods: Identification of selected bacteria (J4 isolate) was based on the 16S rRNA gene sequence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Previously, several studies have demonstrated that biotic and abiotic factors, such as soil type, plant species and development, and fertilization regimes, played essential roles in the recruitment of rhizosphere microbiome ( George et al, 2017 ; Xu et al, 2017 ). Rhizosphere bacteria may provide first line of defense against pathogens causing soil-borne diseases via several mechanisms such as producing antimicrobial substances ( Sulistyani et al, 2021 ), competing for niches ( Bauer et al, 2018 ), triggering plant immune systems ( Teixeira et al, 2019 ), mineralizing of organic materials ( Richard et al, 2017 ), solubilizing recalcitrant phosphorus, or nitrogen fixation ( Alori et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, several studies have demonstrated that biotic and abiotic factors, such as soil type, plant species and development, and fertilization regimes, played essential roles in the recruitment of rhizosphere microbiome ( George et al, 2017 ; Xu et al, 2017 ). Rhizosphere bacteria may provide first line of defense against pathogens causing soil-borne diseases via several mechanisms such as producing antimicrobial substances ( Sulistyani et al, 2021 ), competing for niches ( Bauer et al, 2018 ), triggering plant immune systems ( Teixeira et al, 2019 ), mineralizing of organic materials ( Richard et al, 2017 ), solubilizing recalcitrant phosphorus, or nitrogen fixation ( Alori et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%